Use of Antipsychotics in Delirium - A pilot study to aid development of a protocol for a multinational study - Kristín Brynjarsdóttir 1999- (2025)
Introduction: Delirium is a complex syndrome characterized by disturbances in cognitive function, consciousness, attention and perception, commonly observed among older hospitalised patients. Antipsychotics have been described as “the gold standard” for treating delirium, despite their potential as a risk factor for causing delirium. The lack of clear evidence translates into a paucity of clear prescribing guidance for practice. This study aims to explore the use of antipsychotics in delirium, both as a treatment and as a potential cause, by gathering insights from healthcare professionals. Methods: A qualitative focus group pilot study was conducted using a purposive sample of physicians, clinical pharmacists and nurses with a specialisation in geriatrics, psychiatry and intensive care medicine from Landspítali University Hospital, Iceland (n=9). Data extracted from several previous systematic reviews was collated into an antipsychotic risk stratification table for delirium in adult patients. Two focus groups were carried out to assess the applicability of information to clinical practice. An inductive thematic analysis of responses was performed. Results: The analysis identified four main themes: (1) Antipsychotic use in practice, (2) administration of antipsychotics, (3) statements in the table and (4) layout of the table. Focus group participants view antipsychotics as an alternative when non-pharmacological interventions are not successful or if the patient poses a danger to themselves or others. Certain antipsychotics, predominantly haloperidol, are then used to calm the patient and alleviate their symptoms. Conversely, some antipsychotics listed in the table are considered to be a risk factor for inducing delirium and should therefore be avoided. The risk stratification table was adapted according to the findings from the focus groups and a set of Delphi statements was subsequently developed to inform the protocol of a multinational study. Conclusion: The focus group discussions helped improve the ...